Pengaruh Parents Education Level Dan Lingkungan Belajar Terhadap Motivasi Belajar Siswa - Zahroh, Aminatoz; Suwandi (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine the influence of parents’ education level and learning environment on students’ learning motivation in Madrasah Aliyah Mamba’ul Ulum Megaluh Jombang. This research uses a quantitative approach with ex post facto research type. The sample in this study was 116 students as respondents, and used probability sampling with simple random sampling techniques. Data collection was carried out using a questionnaire distribution with 28 statement items. And using multiple linier regression test data analysis techniques. The results in this study show that. Firstly, there was no partial influence between parents’ education level on student learning motivation with a significance value of T= 0.090 > 0.005. Secondly, there is a partial influence between the learning environment on student learning motivation with a significance value of T= 0.001 < 0.005. Thirdly, there is a simultaneous influence between parents’ education level and learning environment on student learning motivation with a significance value of F= 0.001 < 0,005.